Pathogen life-cycle leaves footprint on the spatial distribution of recruitment of their host plants. (October 2020) - Perea, Antonio J.; Garrido, José L.; Fedriani, Jose M.; Rey, Pedro J.; Alcántara, Julio M.
Abstract: Interactions between established and recruiting plants play an important role in species coexistence in natural plant communities. However, our knowledge on the particular ecological drivers of these interactions is still limited. We use spatial point pattern analysis to study the spatial patterns of recruitment and infection in two plant-pathogen systems, each involving a fungus with a different life cycle: the pair Quercus faginea - Trabutia quercina and the triad Crataegus monogyna - Gymnosporangium sp.- Juniperus oxycedrus . Our results show that T. quercina, an autoecious fungus, may act as a stabilizing mechanism in the population dynamics of Q. faginea . In turn, the effect of the heteroecious Gymnosporangium sp. on C. monogyna recruitment was more related to distance from the alternate host J. oxycedrus than to distance from conspecifics. These results demonstrate that the complexity of pathogen life cycle may impact recruitment and the development of interspecific plant-plant interactions in real plant communities.